The Used of Communication and Mobilization by Lake Chad Research Institute Maiduguri, Borno State, Nigeria - Modu Alhaji Bukar; Mai Dunoma Zanna (Budapest International Research and Critics University, 2023)
This study is to examined the used of communication and mobilization by Lake Chad Research Institute Maiduguri, Borno State. However, in order to set a stage for such examination there are an indispensable need to look at concepts related to communication. The study subdivided into: abstract, introduction, literature review, methodology, findings, conclusion and recommendations. Survey method was adopted some people were interview. The findings show that the organisation prepared to use radio, newsletter, famers help centre, extension guide, famer’s field day, training, Demonstration Farm, magazine communicate to the famers effectively. The study conclude that the organisation ensured the communication between institute and the farmers and other stakeholders is concise, precise and without any form of distortion if their objectives are to be realized. The study recommend that All communication whether verbal or written should be clear, precise and without ambiguity.